Pengaruh Kepercayaan Merek, Persepsi Kualitas, dan Promosi Terhadap Keptusan Pembelian Serta Dampaknya Pada Kepuasan Konsumen di Kalangan Gen-Z (Studi Pada Digital Out of Home Advertising Mobile Led) - Dhafin Syah, Muhammad; Usman, Osly; Krissanya, Nofriska (LANCAH: Jurnal Inovasi dan Tren, 2024)
This research aims to gain new knowledge and analyze the influence of brand trust, perceived quality, and promotions on purchase intention and its impact on costumer satisfaction on digital out of home advertising among Gen Z with a study mobile led. This type of research is quantitative research using a survey method via questionnaires distributed online, with the population used being Gen Z who live in DKI Jakarta. The sampling technique used in this research was a purposive sampling technique with a sample size of 200 respondents. The analysis technique used to process the collected data is validity and reliability testing, using SmartPLS software and hypothesis testing using Structural Equation Modeling (SEM) with SmartPLS software.